Indonesia’s Defense Policy in the Great Power Competition Era - Bagus Jatmiko (The Republic of Indonesia Defense University, 2023)
This study explores Indonesia's defense policy in the current era of great power competition. Great Power Competition (GPC) is the term used to describe hegemony and sphere of influence rivalries between the global powers to exercise their influence and alter the global security constellation for their national interests. The current GPC is dominated by the U.S., China, and Russia, while other nations of the world are trying to find their position within the spectrum of power dynamics towards the global powers by either bandwagoning, balancing, or even hedging. Southeast Asia’s power dynamics are mostly bipolar between the U.S. and China and shape the regional countries' defense policies. As a leading country in the Southeast Asia region, Indonesia is the middle power in the international power constellation and intends to further step up on the power hierarchy. This study aims to highlight the possible formulation of Indonesia's defense policy amidst the GPC era. The study proposes a formulation of Indonesia's defense posture with a qualitative analytical approach based on Mahnken's theory of competitive strategies that is suitable within the spectrum of current power dynamics and appropriate within the national interest framework of foreign policy while weighing both leverage points and dilemmatic challenges. The analysis uses survey data from well-known institutes along with complementary literature interpretation. In conclusion, the article provides a comprehensive finding that Indonesia, like the rest of the nations in the region, prefers balanced relations with the great powers, along with several suggestions on considering the propensity of inward-looking military capabilities, diplomatic competence, and an out-of-sync relationship between domestic politics and foreign policy in formulating defense policy.